(untitled) (Journal of Student Affairs in Africa, 2021)
Since 1994, there has been a doubling in the enrolment of students in South Africa’s public universities. Students, especially first-generation students, face numerous challenges that may impact their subjective perceptions of their well-being. In a milieu of high levels of suicide and depression amongst South Africa’s student population, the understanding of the variables determining students’ subjective well-being (SWB) should be deepened. This article investigates the levels and changes in the SWB of successive groups of first-year students at a comprehensive university in South Africa between 2014 and 2017. It makes use of a fit-for-purpose survey instrument. The results show that the SWB of students is influenced positively by their living arrangements and variables that have a direct influence on the educational environment in which they operate, such as feeling ’at home’ and an overall level of satisfaction of the students’ experience at the university. Negative variables that influence the SWB of students include concerns regarding finances and upcoming tests, and living on campus or within walking distance of campus.